Hydrochemical aspects of water exchange through the bottom of headwater stream in suburban zone on the example of the Malina watercourse in Zgierz (Central Poland) - Ziułkiewicz, Maciej; Grulke, Rafał (Geology, Geophysics and Environment, 2024)
Among the many factors determining the quality of river waters, the influence of the hyporheic zone (HZ) is gaining in importance. Watercourses that exist in the higher parts of catchments are relatively steep and shallow, and the topography of their valleys activate hyporheic flow. The main goal of this work is to assess the impact of the HZ on the hydrochemical state of the head watercourse of the Malina in the suburbs of the city of Zgierz with the focus on biogenic compounds. The riverbed of this stream was researched across two distinct stretches: erosive and accumulative, which differ in the conditions for the hyporheic zone’s interaction with the riverbed. The nutrients are delivered to the stream mainly in the erosive stretch and are related to the inflow of nutrient-rich groundwater from the urbanised catchment. The pollutants transported down by the stream are then delivered to the HZ in the accumulative stretch, where nitrates are denitrified and phosphates are deposited with the suspension. Ammonium nitrogen, in turn, is introduced into the stream from the HZ as a result of either the process of ammonification of organic matter deposited in sediments or inflow with polluted groundwater. The results indicate that the winter season is the most important period in shaping the interaction of river waters with the underlying hyporheic zone, in which the causal side of the relationship should be associated with the subchannel environment, and the effects are recorded in the river waters.